2020
DOI: 10.3390/genes11030287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polycomb Repressive Complex in Malignant Peripheral Nerve Sheath Tumor

Abstract: Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas that can arise most frequently in patients with neurofibromatosis type 1 (NF1). Despite an increasing understanding of the molecular mechanisms that underlie these tumors, there remains limited therapeutic options for this aggressive disease. One potentially critical finding is that a significant proportion of MPNSTs exhibit recurrent mutations in the genes EED or SUZ12, which are key components of the polycomb repressive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 170 publications
(184 reference statements)
0
24
0
Order By: Relevance
“…15 Mosaic loss of H3K27me3 has been observed in a substantial percentage of nerve sheath tumours, synovial sarcomas, and their soft tissue mimics, 24 and its biological significance remains a subject of investigation. 25 In our study, the definitive mosaic loss observed in one of six primary intracranial sarcomas, DICER1-mutant likewise remains mechanistically unexplained. TLE1 has been described as an immunomarker mainly associated with synovial sarcoma.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…15 Mosaic loss of H3K27me3 has been observed in a substantial percentage of nerve sheath tumours, synovial sarcomas, and their soft tissue mimics, 24 and its biological significance remains a subject of investigation. 25 In our study, the definitive mosaic loss observed in one of six primary intracranial sarcomas, DICER1-mutant likewise remains mechanistically unexplained. TLE1 has been described as an immunomarker mainly associated with synovial sarcoma.…”
Section: Discussionmentioning
confidence: 58%
“…It was originally attributed to tumour heterogeneity, hypothesised to reflect heterozygous mutations in some of the tumour cells, while others progressed to develop biallelic mutations in genes encoding the PRC2 subunit, which normally functions to repress transcription through the modification of chromatin 15 . Mosaic loss of H3K27me3 has been observed in a substantial percentage of nerve sheath tumours, synovial sarcomas, and their soft tissue mimics, 24 and its biological significance remains a subject of investigation 25 . In our study, the definitive mosaic loss observed in one of six primary intracranial sarcomas, DICER1 ‐mutant likewise remains mechanistically unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…The review article by Zhang et al discusses the current biological understanding of polycomb repressive complex 2 (PRC2) loss in MPNST, which is a frequently-mutated pathway in these tumors. This article also highlights PRC2 function in normal Schwann cell development and nerve injury repair, in addition to discussing potential therapies that target PCR2 deficiency in tumor cells [ 11 ].…”
mentioning
confidence: 99%
“…SUZ12 loss potentiates the effects of NF1 loss by amplifying RAS-driven transcription through effects on chromatin that triggers an epigenetic switch [ 41 ]. Further detail on the role and function of PRC2 elements in MPNST is found in the review article by Zhang et al dedicated to this topic, also included in this Special Issue on Genomics and Models of Nerve Sheath Tumors [ 67 ]. Collectively, the highly recurrent and specific inactivation of PRC2 components, NF1 , and CDKN2A/B posits their critical and potentially cooperative roles in MPNST pathogenesis.…”
Section: Acquired Mutations During Transformation From Pnfmentioning
confidence: 99%